Effect of 1 MeV electron irradiation on gate contact characteristics of InP-based HEMTs. (1st August 2020) - Sun, Shuxiang; Liu, Hehe; Yang, Bo; Chang, Mingming; Zhong, Yinghui; Li, Yuxiao; Ding, Peng; Jin, Zhi; Wei, Zhichao
Abstract: In this study, the variation of Schottky gate contact characteristics of InP-based HEMTs have been studied with the irradiation fluence range from 1 × 10 14 cm -2 to 1 × 10 16 cm -2 at 1 MeV. The results show that the reverse gate current increases with irradiation fluence, and the reason is that electrons would be released from the induced interface defects and pass through the Schottky barrier under reverse bias. Additionally, the forward gate current decreases and the series resistance of gate contact increases with electron fluence, because the carrier mobility and concentration should be deteriorated by the induced defects in bulk materials and surface state defects at contact interface. It is also found that the ideality factor n increases and the Schottky barrier height Φ B decreases with irradiation fluence, which can be attributed to the radiation induced interface defects at contact interface.